Fast feedback methods in teaching G7 physics - Alcantara, Karen R. (Animo Repository, 2017)
Current literature shows that providing students with feedback plays a vital role in learning and improving student achievement. This study sought to determine the effect of using the Fast Feedback Methods (FFM) on the students’ learning in terms of their mastery of the content and their intrinsic motivation to learn physics. The framework was based on the premise that there has to be a continuous interaction between teacher and students to check on students’ conceptual progress (or lack thereof) and to provide constructive feedback in order to promote learning. The methodology was patterned from a local research of van den Berg (2003). Fast feedback is a method which involves the whole class with the students working individually but at the same pace through a set of questions that may be answered in the form of short responses, sketches, graphs, or drawings. The said approach is given at the end of each lesson as a form of formative assessment. In this study, FFM were not only utilized in the class but were also given through online assignments. Class observations were made to ensure that the conduct of classes adhere to the FFM protocol. An intact section of Grade 7 students from a public school in a major city in the Philippines were purposely selected as respondents. Data for FFM’s effect in terms of students’ mastery were obtained from the formative assessment instruments and posttest, while the intrinsic motivation was explored using a modified Intrinsic Motivation Inventory (IMI). Statistical analysis was performed. Selected students were interviewed to triangulate the results. It was found out that FFM had a positive effect on the students’ mastery of the content. In addition, the IMI result revealed that the students have a high level of intrinsic motivation to learn physics when they are engaged in FFM. © 2017 American Scientific Publishers All rights reserved.